Non-myeloablative conditioning for allogeneic hematopoietic stem cell transplantation in patients with acute myeloid leukemia. The impact of the remission status - Gutiérrez Aguirre, César Homero; Cantú Rodríguez, Olga Graciela; González Llano, Óscar; Salazar Riojas, R.; Martínez González, Odra Lizzette; Jaime Pérez, José Carlos; Gómez Almaguer, David (2005)
Multicentre randomized trials have shown that allogeneic hematopoietic stem cell transplantation (HSCT) is the most effective strategy for preventing relapse in patients in first complete remission (CR) of acute myeloblastic leukemia (AML), offering up to 50% disease-free survival. However in adult patients with good risk AML, allogeneic HSCT is usually indicated in second complete remission or first untreated relapse. We analyzed the outcome of 16 AML patients who received a reduced intensity conditioning regimen for allogeneic HSCT in first or second remission.